RADIO IN TRANSITION: THE AM-FM MIGRATION OF BRUSQUE-SC RADIOS IN THE CONTEXT OF MEDIA CONVERGENCE - Basílio, Nicole Zanon; Basílio, Rodrigo Gonçalves (Seven Editora, 2025)
This article investigates the transformations that have taken place in the commercial broadcasting sector of Brusque-SC following the migration of local stations from the AM to the FM band. Completed by the stations in 2022, this transition is part of the National Policy for the Modernization of Sound Broadcasting, regulated by Brazilian Decree No. 8,139/2013, which aims to improve the technical quality of transmissions and strengthen the competitiveness of regional radio. Adopting a qualitative approach, the research is structured as a case study and is based on documentary research, systematic observation, and semi- structured interviews conducted with managers of the two commercial radio stations in the city that underwent the migration process: Rádio Araguaia and Rádio Cidade. The analysis covers the period from 2021 to 2025, focusing on the impacts of the migration on technical, editorial, and identity-related aspects. The results show that the change of band not only raised the technical standards of the stations but also boosted digital presence strategies and reconfigurations in sound aesthetics and audience relations. The study concludes that the radio stations of Brusque successfully adapted to the logic of media convergence, reconciling technological innovation with the preservation of community ties and local identity. DOI: https://doi.org/10.56238/sevened2025.029-064